2020
DOI: 10.1007/s10989-020-10084-w
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Synthetic Scorpion Venom-Derived Peptide Analogues Against Candida albicans

Abstract: Fungal infections are becoming a serious problem due to their high morbidity and mortality combined with the rise in drug resistance and dearth of new antimycotic drugs. The scorpion venom-derived peptide BmKn2, and its synthetic analogue Kn2–7, were previously observed to have antibacterial activity. These peptides and their d-amino acid analogues (dBmKn2 and dKn2–7) were tested for antifungal activity against drug resistant and clinical isolates of Candida albicans. In planktonic susceptibility studies, dKn2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…An aliquot from each well was plated onto YPD agar. Following incubation, the minimum fungicidal concentration (MFC) was determined to be the lowest concentration of a peptide and antifungal agent, yielding no observable growth (Snyder et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…An aliquot from each well was plated onto YPD agar. Following incubation, the minimum fungicidal concentration (MFC) was determined to be the lowest concentration of a peptide and antifungal agent, yielding no observable growth (Snyder et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Other manuscripts report that the antifungal activity depends on fungal strain ( de Melo et al, 2015 ; Guilhelmelli et al, 2016 ; Machado et al, 2016 ) and antifungal agent ( Ahmadi et al, 2020 ). The scorpion venom D-amino acid analogue dKn2–7 from Mesobuthus martensii showed an amphotericin B-like killing kinetics for C. albicans with rapid onset of antifungal activity ( Snyder et al, 2021 ). It is interesting to note that R. crassicauda venom showed inhibitory activity against C. albicans and C. parapsilosis at a concentration 10–50 times lower than that reported for T. serrulatus venom (1 and 5 mg/mL) against the growth of A. nidulans, A. terreus, P. corylophilum , and P. verrucosum ( Santussi et al, 2017 ).…”
Section: Credit Author Statementmentioning
confidence: 99%
“…This d -isomer is being tested as a strategy for improving stability of the peptide against proteolytic inactivation. Our recent in vitro studies have shown dKn2-7 has greater antifungal potency against Candida albicans biofilms than Kn2-7 [ 8 ]. One possible explanation for the increased antifungal efficacy of dKn2-7 is that d -amino acid peptides are less prone to degradation by endogenous fungal proteases than their corresponding L forms.…”
mentioning
confidence: 99%